Experimental and Theoretical Investigation of the 3sp(d) Rydberg States of Fenchone by Polarized Laser Resonance‐Enhanced‐Multiphoton‐Ionization and Fourier Transform VUV Absorption Spectroscopy. Issue 21 (7th October 2020) - Singh, Dhirendra P.; De Oliveira, Nelson; Garcia, Gustavo A.; Vredenborg, Arno; Powis, Ivan
Abstract: The VUV absorption spectrum of fenchone is re‐examined using synchrotron radiation Fourier transform spectrometry, revealing new vibrational structure. Picosecond laser (2+1) resonance enhanced multiphoton ionization (REMPI) spectroscopy complements this, providing an alternative view of the 3 spd Rydberg excitation region. These spectra display broadly similar appearance, with minor differences that are largely explained by referring to calculated one‐ and two‐photon electronic excitation cross‐sections. Both show good agreement with Franck‐Condon simulations of the relevant vibrational structures. Parent ion REMPI ionization yields with both femtosecond and picosecond excitation laser pulses are studied as a function of laser polarization and intensity, the latter providing insight into the relative two‐photon excitation and one‐photon ionization rates. The experimental circular‐linear dichroism observed in the parent ion yields varies strongly between the 3 s and 3 p Rydberg states, in good overall agreement with the calculated two‐photon excitation circular‐linear dichroism, while corroborating other evidence that the 3p z sub‐state plays no more than a very minor role in the (2+1) REMPI spectrum. Vibrationally resolved photoelectron spectra are recorded with picosecond pulse duration (2+1) REMPI at selected intermediate vibrational excitations. The 3 s intermediate state displays a very strong Δ v =0 propensity on ionization, but the 3 p intermediate evidences more complex vibronic dynamics, and we infer some 3 p →3 s internal conversion prior to ionization. Abstract : Re‐examining Fenchone : Using Fourier Transform VUV photon absorption spectroscopy and (2+1) resonance‐enhanced multiphoton (REMPI) spectroscopy we examine the 3 sp(d) Rydberg states of fenchone. Circular‐linear dichroism observed in the polarized laser REMPI ionization yields is interpreted to help identify the contribution of the 3 p sub‐states. Experimental interpretation is further aided by computational modelling of the two‐photon excitation of the Rydberg intermediates.